Simplified LRFD bridge design - Kim, Jai B., 1934-; Kim, Robert H.; Eberle, Jonathan R. (CRC Press, Taylor & Francis Group, 2013)
Helping readers prepare for the civil and structural PE exam, this book presents numerous design examples that serve as a comprehensive, step-by-step guide to basic bridge design using the AASHTO LRFD Bridge Design Specifications, Fifth Edition. It offers a simplified explanation of load resistance factor design (LRFD) method-based bridge design principles and lists the AASHTO reference section numbers alongside formulas and where topics are introduced, to refer the reader to the primary source material. This is a valuable reference for civil engineering students as well as for practicing engineers.